Satanic rituals and industrial cannibalism. The darkest horror in Tarik Carson - Damonte Luzi, Marcelo (2022)
This article seeks to show that side of the work of the Uruguayan writer Tarik Carson da Silva that focuses on issues such as the esoteric, the satanic and cannibalism, the latter linked especially in its relationship with the commercial industrialization of the human body. For this, the work will make reference to five stories from El hombre olvidado: “Ogedinrof ”, “Interferencias sobre Pérez Loid”, “Demasiado humanos”, “El hombre olvidado” and “Un sueño viejo y oculto”. The horror produced by the ritual control and abuse of bodies, corporal punishment, and the killing for consumption are themes that are repeated in El hombre olvidado (1973), sometimes related to dystopian science fiction literature, others with fantasy or horror literature. In El hombre olvidado the author seems to unleash an attempt to show, in a double movement, the weakness of human and also collide with the human race itself. At the same time the stories seeks: a) to question its constitutive principles; and b) doubt their future possibilities as a species. These questions raise doubts on a whole system of values that, from fiction, show the most terrrible face of the human “animal”.